Will the Truth Set Us Free? An Exploration of CSR Motive and Commitment. (March 2016) - Dare, Julia
Abstract: This article examines why firms engage in Corporate Social Responsibility (CSR). Specifically, it investigates the relationship between a firm's motivation to engage in CSR and the depth of its commitment. I propose that the enduring debate over CSR and financial performance is misaligned, and that scholars should instead focus on the underlying components of CSR engagement. This research sheds light on the motivational antecedents of a firm's engagement in CSR and their effect on CSR commitment. Despite calls for scientific investigation of this linkage, it has received scant attention in the literature. Pursuing this area of research requires the construction of measures of CSR motivation and CSR commitment, as prior work generally lacks objective analysis. I present measures and a research methodology that test hypotheses about how CSR motivation relates to different levels of CSR commitment. The results of this research both validate and challenge current theory. This refined understanding of CSR engagement may enhance firm transparency and accountability to stakeholders. It may reduce the uncertainty in both internal and external assessments of firm CSR and the potential for social and financial impact.